Optimizing C incorporation into magnesium diboride. - Soo, Kien Chen; Kwee, Y. Tan; Kar, Ban Tan; Shaari, Abdul Halim; Kursumovic, Ahmed; MacManus-Driscoll, Judith L. (Institute of Electrical and Electronics Engineers, 2011)
In this work, either SiC or separate Si and C (Si+C) powders of up to 10 weight percentage were in situ reacted with Mg and B (molar ratio of 1:2) and the superconducting properties compared. The latter shows a smaller a-axis lattice cell parameter as compared to the same level of SiC additions, indicating a higher level of C substitution. In those samples, a larger increase in the C-axis is also noticeable and a more severe degradation in the superconducting transition temperature is observed. However, reaction with SiC causes a greater broadening in the transition width. At both 5Kand 20 K, for samples reacted with SiC (up to 5 wt.%) a stronger improvement in the magnitude of critical current density, J c, is obtained. On the other hand, samples reacted with (Si+C) show a weaker dependence on field at 5 K because of higher C substitution. At 20 K, the decreases more rapidly with field for the same level of SiC additions. Hence, for high temperature (20 K) and lowfield (<5 T) applications, reaction with SiC is preferred for obtaining higher J c (H).